2017
DOI: 10.1186/s13643-017-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, double-blind, placebo-controlled trials of non-individualised homeopathic treatment: systematic review and meta-analysis

Abstract: BackgroundA rigorous systematic review and meta-analysis focused on randomised controlled trials (RCTs) of non-individualised homeopathic treatment has not previously been reported. We tested the null hypothesis that the main outcome of treatment using a non-individualised (standardised) homeopathic medicine is indistinguishable from that of placebo. An additional aim was to quantify any condition-specific effects of non-individualised homeopathic treatment.MethodsLiterature search strategy, data extraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
181
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(200 citation statements)
references
References 28 publications
2
181
0
17
Order By: Relevance
“…In total, 61 systematic reviews and meta‐analyses were included in qualitative synthesis (Altunç et al, ; Banerjee et al, ; Baranowsky et al, ; Barnes et al, ; Bellavite et al, ; Boehm et al, ; Bornhöft et al, ; Catalá‐López et al, ; Cooper & Relton, ; Cucherat et al, ; Davidson et al, ; De Silva et al, ; Ernst & Barnes, ; Ernst & Pittler, ; Ernst, ;Györik & Brutsche, ; Heirs & Dean, ; Holdcraft et al, ; Jonas et al, ; Kassab et al, ; Kleijnen et al, ; Levi et al, ; Linde al., ; Linde & Melchart, ; Linde et al, ; Long & Ernst, ; Loo & Tang, ; Mathie et al, ; Mathie et al, ; Mathie et al, ; Mathie, ; McCarney et al, ; McCarney et al, ; Meehan et al, ; Milazzo et al, ; Morrison et al, ; Owen & Green, ; Peckham et al, ; Perry et al, ; Pilkington, Kirkwood, Rampes, Fisher, & Richardson, ; Pilkington, Kirkwood, Rampes, Fisher, & Richardson, ; Reid et al, ; Rostock & Saller, ; Subhranil & Munmun, ; Schneider et al, ; Shang et al, ; Smith, ; Sterne et al, ; Stevinson & Ernst, ; Struijs & Kerkhoffs, ; Terry et al, ; Thandar et al, ; van der Wouden et al, ; Vernon et al, ; Wiesenauer & Lüdtke, ). Data about the efficacy of homoeopathy are shown in Table .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…In total, 61 systematic reviews and meta‐analyses were included in qualitative synthesis (Altunç et al, ; Banerjee et al, ; Baranowsky et al, ; Barnes et al, ; Bellavite et al, ; Boehm et al, ; Bornhöft et al, ; Catalá‐López et al, ; Cooper & Relton, ; Cucherat et al, ; Davidson et al, ; De Silva et al, ; Ernst & Barnes, ; Ernst & Pittler, ; Ernst, ;Györik & Brutsche, ; Heirs & Dean, ; Holdcraft et al, ; Jonas et al, ; Kassab et al, ; Kleijnen et al, ; Levi et al, ; Linde al., ; Linde & Melchart, ; Linde et al, ; Long & Ernst, ; Loo & Tang, ; Mathie et al, ; Mathie et al, ; Mathie et al, ; Mathie, ; McCarney et al, ; McCarney et al, ; Meehan et al, ; Milazzo et al, ; Morrison et al, ; Owen & Green, ; Peckham et al, ; Perry et al, ; Pilkington, Kirkwood, Rampes, Fisher, & Richardson, ; Pilkington, Kirkwood, Rampes, Fisher, & Richardson, ; Reid et al, ; Rostock & Saller, ; Subhranil & Munmun, ; Schneider et al, ; Shang et al, ; Smith, ; Sterne et al, ; Stevinson & Ernst, ; Struijs & Kerkhoffs, ; Terry et al, ; Thandar et al, ; van der Wouden et al, ; Vernon et al, ; Wiesenauer & Lüdtke, ). Data about the efficacy of homoeopathy are shown in Table .…”
Section: Resultsunclassified
“…Twenty‐five reviews demonstrated that homoeopathy efficacy is comparable to placebo (Altunç et al, ; Catalá‐López et al, ; Cooper & Relton, ; De Silva et al, ; Ernst, ; Ernst & Barnes, ; Ernst & Pittler, ; Györik & Brutsche, ; Heirs & Dean, ; Mathie et al, ; McCarney et al, ; Meehan et al, ; Milazzo et al, ; Reid et al, ; Subhranil & Munmun, ; Shang et al, ; Smith, ; Sterne et al, ; Thandar et al, ; van der Wouden et al, ; Vernon et al, ), twenty reviews did not come to a definite conclusion (Banerjee et al, ; Davidson et al, ; Ernst, ; Kleijnen et al, ; Linde et al, ; Long & Ernst, ; Loo & Tang, ; Mathie et al, ; Mathie, ; McCarney et al, ; Morrison et al, ; Owen & Green, ; Perry et al, ; Pilkington et al, ; Pilkington et al, ; Rostock & Saller, ; Stevinson & Ernst, ; Struijs & Kerkhoffs, ; Terry et al, ), and sixteen reviews concluded that homoeopathy has some effect beyond placebo (Baranowsky et al, ; Barnes et al, ; Bellavite et al, ; Boehm et al, ; Bornhöft et al, ; Cucherat et al, ; Holdcraft et al, ; Jonas et al, ; Kassab et al, ; Levi et al, ; Linde & Melchart, ; Linde et al, ; Mathie et al, ; Peckham et al, ; Schneider et al, ; Wiesenauer & Lüdtke, ).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…One part of the group gets the verum (remedy) and the other part the placebo [3,4]. But it is not possible to find people who need the same remedies at the same time, even if they have similar symptoms.…”
Section: Homeopathymentioning
confidence: 99%
“…Therefore homeopathy is accused to be of being a humbug, a placebo. Many publications describe very critical [1,2] and many publications describe successful homeopathy [3,4]. For years many theories have…”
Section: Introductionmentioning
confidence: 99%